U‐PB LA‐ICP‐MS DATING OF ZIRCONS FROM SUBVOLCANICS OF THE BIMODAL DYKE SERIES OF THE WESTERN TRANSBAIKALIA: TECHNIQUE, AND EVIDENCE OF THE LATE PALEOZOIC EXTENSION OF THE CRUST - M. D. Buyantuev; V. B. Khubanov; T. T. Vrublevskaya (Геодинамика и тектонофизика, 2017)
Our study investigates a possibility of using isotope ratios of U‐Th‐Pb system in zircon analysis by the LA‐ICP‐MS technique and monitoring of precision, convergence and accuracy. New U‐Pb isotope‐geochronological data has been obtained for the salic and mafic members of the bimodal Late Paleozoic series of subparallel dykes in the central part of the Western Transbaikalia. It is shown that a series of subparallel dykes (290–280 Ma) gives evi‐ dence of extension of the continental crust at the final stage of the Late Paleozoic granitoid magmatism. Similar ages of zircons in the salic and mafic subvolcanic rocks confirm the geological indicators of the coexistence and interactions between the magmas of contrasting compositions.